2021
DOI: 10.1186/s12711-021-00662-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for and localization of proposed causative variants in cattle and pig genomes

Abstract: Background This paper reviews the localization of published potential causative variants in contemporary pig and cattle reference genomes, and the evidence for their causality. In spite of the difficulties inherent to the identification of causative variants from genetic mapping and genome-wide association studies, researchers in animal genetics have proposed putative causative variants for several traits relevant to livestock breeding. Results For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 151 publications
0
15
0
Order By: Relevance
“…Whole-genome sequence data has already been applied in genome-wide association studies (GWAS) to identify variants associated with a variety of traits in livestock [ 2 , 32 34 ], including pigs [ 35 , 36 ]. However, the fine-mapping of causal variants remains challenging due to the pervasive long-range linkage disequilibrium across extremely dense variants [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome sequence data has already been applied in genome-wide association studies (GWAS) to identify variants associated with a variety of traits in livestock [ 2 , 32 34 ], including pigs [ 35 , 36 ]. However, the fine-mapping of causal variants remains challenging due to the pervasive long-range linkage disequilibrium across extremely dense variants [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Verification, validation and fine-mapping of quantitative trait loci (QTL) derived from genome-wide association studies can benefit from imputed sequence data [ 14 ], although the relatively high level of linkage disequilibrium in pig breeding populations makes detection of causative variants more difficult. Combining statistical, bioinformatic, and functional information, such as genetic associations, linkage disequilibrium, annotation, and functional genomic data, might optimize such detection (e.g., [ 16 18 ]) and, in addition, will increase the number of QTL and the proportion of variance explained by these QTL, compared to the use of a lower marker density [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we did not find any candidate variant in AGPAT1 or AGPAT3, and the few candidate variants in AGPAT2 and AGPAT4 were discarded because they were located in introns. A typical criterion for prioritizing candidate variants is to limit the search to coding and promoter regions, since the prediction of the potential effects of variants located in non-coding regions from DNA sequence is not straightforward (Johnsson & Jungnickel, 2021). However, in some instances non-coding variants, which may have regulatory functions, have been proposed as candidate variants (Ryan et al, 2012;Solé et al, 2021;Van Laere et al, 2003), while variants in coding regions have often been found to have a small impact on complex traits Abbreviations: C16:0, palmitic acid; C18:0, stearic acid; C16:1n-7, palmitoleic acid; C18:1n-7, vaccenic acid; C18:1n-9, oleic acid; C18:2n-6, linoleic acid; C18:3n-3, linolenic acid; C20:4n-6, arachidonic acid; MUFA, monounsaturated fatty acids; PUFA, polyunsaturated fatty acids; SFA, saturated fatty acids.…”
Section: Preselection Of Candidate Variants In the Agpat Gene Familymentioning
confidence: 99%